Water Infiltration into a Frozen Soil with Simultaneous Melting of the Frozen Layer. Issue 1 (21st November 2012) - Watanabe, Kunio; Kito, Tetsuya; Dun, Shuhui; Wu, Joan Q.; Greer, R. Cory; Flury, Markus
Abstract : Understanding water infiltration into frozen soil is important for preventing soil erosion and managing soil water and nutrients. In this study, we performed a column experiment on infiltration through frozen soil using a variably‐saturated silt loam. Three soil columns (7.8 cm i.d., 35 cm long), with three different initial soil water contents, were cooled from the top to form a frozen layer of the same thickness. The columns were instrumented with 34 thermocouples, seven time‐domain reflectometry (TDR) probes, and seven tensiometers. Water at a temperature of 3.5°C was applied to the top of the columns with a 15‐cm constant head. We monitored ice and liquid water contents, temperatures, and the position of the infiltration front. Three phases of infiltration were observed: (i) no infiltration at the beginning, (ii) slow infiltration as the infiltration front advanced through the frozen layer, and (iii) increased infiltration as the infiltration front advanced through the unfrozen soil below the frozen layer. The duration of each phase became longer with increasing initial soil water content as the infiltration rate of each phase decreased. The volumetric ice content and thickness of the frozen layer controlled the infiltration process. We use a capillary bundle model to characterize the hydraulic conductivity as a function of ice content during infiltration. Based on our experimental data and results, we mechanistically describe the water infiltration into frozen soil.